THE EFFECT OF ACCOUNTABILITY AND VALUE FOR MONEY ON FINANCIAL PERFORMANCE WITH GOVERNMENT ACCOUNTING STANDARDS AS MODERATION VARIABLES - Muhammad Ilham Muliang; Haliah; Darmawati (International Journal of Multidisciplinary Research and Studies, 2023)
Muhammad Ilham M, with the title The Effect of Accountability and Value for Money on Financial Performance with Government Accounting Standards as a Moderating Variables. (as supervisor haliah and Darmawati). This study aims to examine accountability and value for money on financial performance with government accounting standards as a moderating variable. The research was conducted at the SKPD of Pinrang Regency for a period of two months, starting from October 2022 to November 2022. This study uses quantitative research methods, using primary data collected by giving statement questionnaires to 60 respondents. The data analysis method used to test the hypothesis is to use multiple linear regression with the help of Smart PLS 4.0 software. The results of the study show that the variables of accountability and value for money have a positive and significant impact on financial performance. Whereas in the moderation effect in this study, government accounting standards can moderate the effect of accountability on regional financial management and the effect of value for money on financial performance, the results can strengthen these variables.